Analysis of Capital Structure, Leverage, and Sales Growth in Term of Tax Avoidanve - Arianti, Baiq Fitri; Soesila, Byas (Universitas Negeri Malang, 2025)
The large number of companies involved in tax avoidance practices by manipulating profits should be a concern for the government in strengthening the tax system in Indonesia. The purpose of this study is to analyze and empirically examine the influence of companies in the consumer non-cyclicals sector on tax avoidance, viewed from the aspects of capital structure, leverage, and sales growth. This research involves all consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totaling 125 companies, with a sample of 30 companies. The study uses a quantitative approach through panel data regression analysis with the help of EViews version 12. The findings of this study show that capital structure does not have a significant effect on tax avoidance, while leverage has an effect on tax avoidance, and sales growth also has an effect on tax avoidance. Although many studies on tax avoidance have been conducted, studies examining leverage using the proxy of Degree of Financial Leverage (DFL) in consumer non-cyclicals sector companies remain limited. The implications of this study reinforce agency theory, which posits that information asymmetry between owners and managers can encourage managers to maximize profits through tax avoidance. These results can also serve as a consideration in designing stricter fiscal policies targeting companies with high potential for tax avoidance, emphasizing the need for a fairer and more efficient tax system, as well as the necessity for strict sanctions to curb tax avoidance practices among large corporations